ANALISIS MUSIM PENANGKAPAN DAN TINGKAT PEMANFAATAN IKAN LAYUR (TRICHIURUS SP) DI PERAIRAN PALABUHANRATU, SUKABUMI, JAWA BARAT - Harjanti, Retno; Wibowo, Pramono; Hapsari, Trisnani (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
The commonly activity of hairtail fish catching in waters of Palabuhanratu is used handline. The average of hairtail fish production in this area reaches 174 tonnes per year. One of the things that supported the succesfully of hairtail fish capture is knowledge the fishing season of hairtail fish This research aimed to understand the potential of sustainable resources, the fishing season of hairtail fish, as well as exploitation rate of hairtail fish. This research was used descriptif methods with kind of case study research. Data analysis was used statistic methods, moving average methods and surplus production model with logistic growth function. Management model of trichiurus fish resources based on maximum economic yield, maximum sustainable yield and open access section. Result showed that EMSY was 8710 trips/year while CMSY was 294,92 ton/year, in actually effort was 8370 trips/ year and C was 176 ton/ year . Based on the index was known that the peak fishing season fishing occurs in April. The highest utilization rate during the last 9 years in 2007 which is 109%.